A Cultural Phenomenology of Qigong: Qi Experience and the Learning of a Somatic Mode of Attention. (8th July 2022) - Lazzarelli, Alessandro
Abstract: In Chinese body culture, the construct of qi 氣—literally translated as breath or energy—is at the heart of several programs of self‐cultivation, as well as other domains of bodily knowledge related to the subjective and inter‐subjective realm of everyday life. Also, among Chinese societies and communities, discourses on qi have assumed social significance in the milieus of politics, religion, and popular culture. Therefore, it appears to be the case that a concern for the qi experience is significant to both the Chinese sensorium and its sociocultural context. However, while this category is ubiquitous, we are still left with the question of how people learn, elaborate, and make sense of it. By drawing from an in‐depth ethnographic study of a group of neidan qigong 內丹氣功 practitioners in Taipei, Taiwan, the aim of this article is twofold. To a greater extent, it investigates what role qigong, a mind‐body practice to cultivate and balance the vital energy, plays in the individual learning, elaboration, and understanding of the qi sensory experience. To a lesser extent, it considers this case study in the broader sociocultural context, in order to demonstrate that a first‐person approach to the qi experience can contribute to understanding the dynamics between embodied learning, consciousness, and society.